2023
DOI: 10.3389/fimmu.2023.1143980
|View full text |Cite
|
Sign up to set email alerts
|

SnoRNA and lncSNHG: Advances of nucleolar small RNA host gene transcripts in anti-tumor immunity

Abstract: The small nucleolar RNA host genes (SNHGs) are a group of genes that can be transcript into long non-coding RNA SNHG (lncSNHG) and further processed into small nucleolar RNAs (snoRNAs). Although lncSNHGs and snoRNAs are well established to play pivotal roles in tumorigenesis, how lncSNHGs and snoRNAs regulate the immune cell behavior and function to mediate anti-tumor immunity remains further illustrated. Certain immune cell types carry out distinct roles to participate in each step of tumorigenesis. It is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 135 publications
(131 reference statements)
1
11
0
Order By: Relevance
“…In addition to these canonical functions in the nucleolus, snoRNAs are involved in non-canonical mechanisms, such as the biogenesis of piwi-interacting RNA (piRNA) and snoRNA-derived fragments (sdRNA), the derivation of certain microRNAs (miRNAs), tRNA methylation, and rRNA acetylation [ 9 ]. Moreover, snoRNAs turned out to play diverse roles in RNA-related processes, regulating splicing and chromatin accessibility [ 9 ]. All of these epigenetic processes play a crucial role in the proper execution of cellular bioactivities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these canonical functions in the nucleolus, snoRNAs are involved in non-canonical mechanisms, such as the biogenesis of piwi-interacting RNA (piRNA) and snoRNA-derived fragments (sdRNA), the derivation of certain microRNAs (miRNAs), tRNA methylation, and rRNA acetylation [ 9 ]. Moreover, snoRNAs turned out to play diverse roles in RNA-related processes, regulating splicing and chromatin accessibility [ 9 ]. All of these epigenetic processes play a crucial role in the proper execution of cellular bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…SNHGs, which can be protein-coding or noncoding genes, produce primary transcripts in the nucleus. These transcripts undergo splicing, with exons directed to cytoplasmic functions as either protein-coding mRNAs or noncoding RNAs (long noncoding RNA SNHGs; lncSNHGs) ( Figure 1 (3b): Spliced lncSNHG/mRNA) [ 9 , 18 , 19 ]. Introns yield mature snoRNAs, which then localize to the nucleolus and Cajal bodies ( Figure 1 (3a): Post-transcription processing) [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al have found that a long non-coding RNA (lncRNA), which named PRRT3-AS1, could be treated as a potential biomarker for melanoma treatment. 4 Another study discovered P4HA1 as a biomarker associated with poor prognosis in primary melanomas. 5 However, the clinical application of therapeutic targets and biomarkers in melanoma is still limited due to its complex and immune-related heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…As several studies have mentioned, the potential of biomarkers in the identification and prognosis of melanoma is highlighted. For instance, Zhang et al have found that a long non‐coding RNA (lncRNA), which named PRRT3‐AS1, could be treated as a potential biomarker for melanoma treatment 4 . Another study discovered P4HA1 as a biomarker associated with poor prognosis in primary melanomas 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation